Venus express - The first European mission to Venus - Svedhem, H; Titov, D; McCoy, D; Lebreton, J; Barabash, S; Bertaux, J; Drossart, P; Formisano, V; Haeusler, B; Korablev, O; Markiewicz, W; Nevejans, D; et al. (2007)
Venus Express is the first European mission to planet Venus. The mission aims at a comprehensive investigation of Venus atmosphere and plasma environment and will address some important aspects of the surface physics from orbit. In particular, Venus Express will focus on the structure, composition, and dynamics of the Venus atmosphere, escape processes and interaction of the atmosphere with the solar wind and so to provide answers to the many questions that still remain unanswered in these fields. Venus Express will enable a breakthrough in Venus science after a long period of silence since the period of intense exploration in the 1970s and the 1980s. The payload consists of seven instruments. Five of them were inherited from the Mars Express and Rosetta projects while two instruments were designed and built specifically for Venus Express. The suite of spectrometers and imaging instruments, together with the radio-science experiment, and the plasma package make up an optimised payload well capable of addressing the mission goals to sufficient depth. Several of the instruments will make specific use of the spectral windows at infrared wavelengths in order to study the atmosphere in three dimensions. The spacecraft is based on the Mars Express design with minor modifications mainly needed to cope with the thermal environment around Venus, and so a very cost-effective mission has been realised in an exceptionally short time. The spacecraft was launched on 9 November 2005 from Baikonur, Kazakhstan, by a Russian Soyuz-Fregat launcher and arrived at Venus on 11 April 2006. Venus Express will carry out observations of the planet from a highly elliptic polar orbit with a 24-h period. In 3 Earth years (4 Venus sidereal days) of operations, it will return about 2 Tbit of scientific data. Telecommunications with the Earth is performed by the new ESA ground station in Cebreros, Spain, while a nearly identical ground station in New Norcia, Australia, supports the radio-science investigations. © 2007 Elsevier Ltd. All rights reserved.